If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -151 = -1x + 6(-6x + 3) Reorder the terms: -151 = -1x + 6(3 + -6x) -151 = -1x + (3 * 6 + -6x * 6) -151 = -1x + (18 + -36x) Reorder the terms: -151 = 18 + -1x + -36x Combine like terms: -1x + -36x = -37x -151 = 18 + -37x Solving -151 = 18 + -37x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '37x' to each side of the equation. -151 + 37x = 18 + -37x + 37x Combine like terms: -37x + 37x = 0 -151 + 37x = 18 + 0 -151 + 37x = 18 Add '151' to each side of the equation. -151 + 151 + 37x = 18 + 151 Combine like terms: -151 + 151 = 0 0 + 37x = 18 + 151 37x = 18 + 151 Combine like terms: 18 + 151 = 169 37x = 169 Divide each side by '37'. x = 4.567567568 Simplifying x = 4.567567568
| 2X+3=(X+5)*(X+5) | | 11q-7q=20 | | -20y+1=2-16y+11 | | 10.66+y=28.66 | | 3x-1=(X+5)*(X+5) | | 3x-21=9x+54 | | -5-8(1-3k)=19 | | 13p=-36 | | x^2+5x=3x+24 | | x^2-4.07x+2.71=0 | | (x+3)(x-7)(x+8)=0 | | 10.66+7=28.66 | | 9m-4m=15 | | f(0.75)=2(0.75)+4 | | 5b+3b=8 | | (4z-1)2= | | 0=5x^4-90x^2 | | 2x-3-6x-4=5 | | (x+1)(x+2)=11+(x)(x) | | 0.55555x-4=2+x-18 | | x^2+3x-147=0 | | 5f+3=29 | | 72-12y+y=5 | | 3x+2x-15= | | x^2+3-147=0 | | 3/4b=6 | | 17.17+w=28.78 | | 2x+12=3x-7 | | 0.15x+1.2=0.4x-0.8 | | 20=(-4f+6)+14 | | 2x^4-6x^2+5x-15=0 | | factorx^2-5x-2=0 |